HUBUNGAN DEPRESI DENGAN TINGKAT RELIGIUSITAS LANSIA PENDERITA DM II PADA KELOMPOK PROLANIS DI YOGYAKARTA - SUSANTI P.A.E; ROHASLIA B; SOEWADI . (JURNAL ILMIAH KOHESI, 2021)
Changes in people's lifestyles such as changes in diet and decreased physical activity can lead to a variety of metabolicdiseases. One of the metabolic diseases is diabetes mellitus (Prise, 2005). Various epidemiological studies show a tendencyto increase the incidence and prevalence of TYPE 2 DM worldwide, about 90% of cases. Diabetics have a 3-fold risk ofdepression compared to society in general. Religious approach is one of the spiritual approaches to metal disorders such asdepression ((Setyonegoro, 1985). To find out the relationship between depression and the level of religiosity in elderly familyphysician prolanis group in Yogyakarta. This research is an observational study with cross-sectional design. The subject ofthis study was the elderly yoyakarta family doctor prolanis group. Depression levels were assessed with geriatric depressionscale (GDS) instruments and religiosity levels were assessed with religiosity questionnaires. The data is analyzed withunivariate and bivariate. Of the 37 respondents obtained a meaningful relationship between depression and religiosity levelin the elderly group prolanis family doctor was shown correlation with the value r 0.457 with p 0.004. There is a relationshipbetween depression and the level of religiosity of dm ii sufferers in the group of family doctor prolanis in Yogyakarta.